Challenges in the Diagnosis of Invasive Candidiasis - Jagdeesh Natesan; Suganthini Krishnan (New Advances in Medicine and Medical Science Vol. 2, 2023)
This review provides a brief overview of the evolution of candida diagnostics, difficulties in interpreting test results, their strengths and limitations, and guide clinicians interpret test results from a clinical perspective. Invasive candidiasis (IC) is an important cause of nosocomial blood stream infections and deep tissue infections, associated with a high mortality of 30%. Early diagnosis and timely initiation of antifungal therapy is crucial. Most advanced blood culture systems detect a dismal 50% of IC, and cannot be relied upon as sole diagnostic tools. Hence it is imperative that non -culture based diagnostic tests are developed, validated and standardized to enhance the diagnostic sensitivity of IC. The last three decades have witnessed the introduction of several different diagnostic tests, most of which haven’t been successful. Additionally, it gives medical professionals a manual for how to interpret test results from a clinical standpoint so that they can use antifungal medications wisely. Such a strategic approach would definitely facilitate early diagnosis and treatment of IC and decrease mortality in these patients.